Differentiation of Bacillus pumilus and Bacillus safensis Using MALDI-TOF-MS - Branquinho, Raquel; Sousa, Clara; Lopes, João; Pintado, Manuela E.; Peixe, Luísa V.; Osório, Hugo (PloS one, 2014)
Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) despite being increasingly used as a method for microbial identification, still present limitations in which concerns the differentiation of closely related species. Bacillus pumillus and Bacillus safensis, are species of biotechnological and pharmaceutical significance, difficult to differentiate by conventional methodologies. In this study, using a well-characterized collection of B. pumillus and B. safensis isolates, we demonstrated the suitability of MALDI-TOF-MS combined with chemometrics to accurately and rapidly identify them. Moreover, characteristic species-specific ion masses were tentatively assigned, using UniProtKB/Swiss-Prot and UniProtKB/TrEMBL databases and primary literature. Delineation of B. pumilus (ions at m/z 5271 and 6122) and B. safensis (ions at m/z 5288, 5568 and 6413) species were supported by a congruent characteristic protein pattern. Moreover, using a chemometric approach, the score plot created by partial least square discriminant analysis (PLSDA) of mass spectra demonstrated the presence of two individualized clusters, each one enclosing isolates belonging to a species-specific spectral group. The generated pool of species-specific proteins comprised mostly ribosomal and SASPs proteins. Therefore, in B. pumilus the specific ion at m/z 5271 was associated with a small acid-soluble spore protein (SASP O) or with 50S protein L35, whereas in B. safensis specific ions at m/z 5288 and 5568 were associated with SASP J and P, respectively, and an ion at m/z 6413 with 50S protein L32. Thus, the resulting unique protein profile combined with chemometric analysis, proved to be valuable tools for B. pumilus and B. safensis discrimination, allowing their reliable, reproducible and rapid identification.